(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
Herbaceous biomass can be obtained using delayed harvesting method with moisture content less than 15% and directly densified without drying. Size reduction experiments of common reed stalks as cutting, flattening and densification have been carried out. As the result of reed stalk flattening, more than 8 strips can be obtained from this tubular structure. Average energy consumption 273 – 380 J kg-1 had been stated for reed stalk flattening. Specific cutting energy Escq value varies in 8 – 16 kJ m-2 in dependence of punch orientation angle according cross-section of reed specimen. Specific cutting energy for flattened stalk materials for reed density 600 kg m-3, varies Esc=13.3 – 27 J m kg-1. Densification experiments of compositions from peat particles, coarse wheat stalk and reed material particles from (1 - 2 mm) group with pressure 230 MPa indicated influence of peat proportion. Density 1.0 g cm-3 has been obtained in densification of straw stalk material particle compositions with peat, if peat proportion exceeds 20%.